2011
DOI: 10.1073/pnas.1108399108
|View full text |Cite
|
Sign up to set email alerts
|

Database independent proteomics analysis of the ostrich and human proteome

Abstract: Mass spectrometry (MS)-based proteome analysis relies heavily on the presence of complete protein databases. Such a strategy is extremely powerful, albeit not adequate in the analysis of unpredicted postgenome events, such as posttranslational modifications, which exponentially increase the search space. Therefore, it is of interest to explore "database-free" approaches. Here, we sampled the ostrich and human proteomes with a method facilitating de novo sequencing, utilizing the protease Lys-N in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…S5). These findings are in line with previous reports describing that peptides with a strong basic N terminus generate more straightforward and easy-to-interpret MS/MS spectra in ETD (19).…”
Section: Resultssupporting
confidence: 92%
“…S5). These findings are in line with previous reports describing that peptides with a strong basic N terminus generate more straightforward and easy-to-interpret MS/MS spectra in ETD (19).…”
Section: Resultssupporting
confidence: 92%
“…We previously showed that peptides that carry two protons at the N-terminus fragment predominantly into N-terminal c fragment ions during electron-transfer dissociation (ETD), facilitating straightforward peptide sequencing even when no a priori knowledge of the protein sequence is available. , Here, we analyzed thousands of peptides generated by LysargiNase or trypsin from a Jurkat cell lysate using ETD or HCD to investigate whether LysargiNase represents a suitable protease for ladder sequencing of peptides. We describe the fragmentation characteristics of these K/R­(X) n (i.e., LysargiNase) and (X) n K/R (i.e., trypsin) peptides during chromatographic separation and gas-phase fragmentation and show the consequences of mirroring the location of the basic residue on peptide fragmentation, with the aim of probing the broader usability of LysargiNase in (phospho)­proteomics applications.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins can also interact with other molecules like RNA, DNA and metabolites. These complexes play crucial roles in regulatory processes, signalling cascades, cellular functions, and their inability to interact can result in their function being lost ( Altelaar et al, 2012 ; Ma and Johnson, 2012 ). Tranche is one of the few public repositories that can manage this type of data at the moment, and it is based on an encrypted peer-to-peer system that stores data in numerous servers across the world.…”
Section: Proteomicsmentioning
confidence: 99%